Comparison of sensitivity and specificity of Wells rule and the revised Geneva score with CT angiography in identifying patients with pulmonary embolism - Abedini, Atefeh; Sadeghi, Mohsen; Kiani, Arda; Edalatnoor, Behnoosh (Researcher Bulletin of Medical Sciences, 2023)
Abstract Background and Objective: The use of angiography is the gold standard in the diagnosis of pulmonary embolism (PE). However, the invasive side effects and being less accessible, it is rarely performed. This study sought to determine the sensitivity, specificity, accuracy and positive and negative predictive value of Wells Rule and Revised Geneva Score in identifying patients with pulmonary embolism. Materials and Methods: This cross-sectional study was performed on 214 patients with suspected pulmonary embolism who referred to Masih Daneshvari Hospital in Tehran, Iran in 2020. The researchers recorded the CT angiographic findings of patients suspected of having pulmonary embolism. All the patients were evaluated based on each of the Wells Rule and revised Geneva score. Finally, the sensitivity and specificity of each score was evaluated in comparison with CT angiography as the gold standard method in the diagnosis of pulmonary embolism. Results: The overall mean scores of the Revised Geneva Score and Wells Rule were 99.2± 33.6 and 68.2± 96.3, respectively. The sensitivity, specificity and accuracy of the Revised Geneva Score were 90.6, 47.4 and 72%, respectively. The sensitivity, specificity and accuracy of the Wells Rule were 71.8, 75.3 and 77%, respectively. The positive predictive values (PPV) for the Wells Rule and the Revised Geneva Score were 67.5 and 77.8, respectively. Finally, the negative predictive values (NPV) for the Wells Rule and Revised Geneva Score were 80.7 and 68.9, respectively. Conclusions: The Revised Geneva Score is highly accurate in diagnosing pulmonary embolism. The score could be used as a non-invasive clinical evaluation tool in the diagnosis of PE.